Separation of Trace Amount Cu (II) Using Octadecyl Silica Membrane Disks - Nano Graphene Modified N, N -disalicylideneethylenediamine - Ali Moghimi (Journal of Chemical Health Risks, 2014)
A simple, highly sensitive, accurate and selective method was presented for determination of trace amounts of Cu (II) in water samples. The stability of an N, N´ -disalicylideneethylenediamine modified Nano Geraphene especially in concentrated hydrochloric acid was studied which used as a recycling and pre-concentration reagent for further uses of N, N´-disalicylideneethylenediamine modified Nano Geraphene. The method was based on N, N´ -disalicylideneethylenediamine modified Nano Gerapheneof Cu (II) on surfactant coated C18, modified with a N, N´ -disalicylideneethylenediamine modified Nano Geraphene. The retained ions were then eluted with 4 ml of 4 M nitric acid and determined by flame atomic absorption spectrometry (FAAS) at 283.3 nm for Cu. The influence of flow rates of sample and eluent solutions, pH, breakthrough volume, effect of foreign ions were investigated on chelation and recovery. (1.5 g of surfactant coated C18 adsorbs 40 mg of the Schiff’s base which in turn can retain 15.2±0.8mg of ion) The limit of detection (3σ) for Cu (II) was found to be 3.20 ng l -1. The enrichment factor for both ions was 100. The mentioned method was successfully applied on determination of Cu in different water samples. The ions were also speciated by means of three- column system.